2008
DOI: 10.1007/s11063-007-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Approximation of Discontinuous Functions by Neural Networks

Abstract: In this paper, we give a constructive proof that a real, piecewise continuous function can be almost uniformly approximated by single hidden-layer feedforward neural networks (SLFNNs). The construction procedure avoids the Gibbs phenomenon. Computer experiments show that the resulting approximant is much more accurate than SLFNNs trained by gradient descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…We note that results for continuous functions indicate that functions that have better smoothness properties can have lower approximation error for a particular number of neurons [32,10,33]. For discontinuous functions, Llanas et al [24] showed that a real and piecewise continuous function can be approximated in an almost uniform way. However, Llanas et al [24] also noted that piecewise continuous functions when trained with gradient descent methods require many neurons and training iterations, and yet do not give very good results.…”
Section: Related Workmentioning
confidence: 78%
See 1 more Smart Citation
“…We note that results for continuous functions indicate that functions that have better smoothness properties can have lower approximation error for a particular number of neurons [32,10,33]. For discontinuous functions, Llanas et al [24] showed that a real and piecewise continuous function can be approximated in an almost uniform way. However, Llanas et al [24] also noted that piecewise continuous functions when trained with gradient descent methods require many neurons and training iterations, and yet do not give very good results.…”
Section: Related Workmentioning
confidence: 78%
“…For discontinuous functions, Llanas et al [24] showed that a real and piecewise continuous function can be approximated in an almost uniform way. However, Llanas et al [24] also noted that piecewise continuous functions when trained with gradient descent methods require many neurons and training iterations, and yet do not give very good results. These results suggest that continuous rotation representations might perform better in practice.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies proved that the universal approximation property of a multi-layer feedforward neural network holds for unbounded activation function such as the rectifier function we used in this paper [41]. Studies also proved that a neural network can approximate a discontinuous function [42], and in practice the distinction between continuous and discontinuous functions is not an important factor for the approximation capacity of a neural network [43]. The approximation theorem states that, for any > 0, we are able to construct a multi-layer feed-forward neural network F such that:…”
Section: B Solution Overviewmentioning
confidence: 77%
“…However, most of the works prescribed need the assumption that the function to be approximated by neural network is continuous. In this work, with resorting to the techniques described in [29,23], we extend the discussion to approximation and compensation for piecewise discontinuous function within the proposed control framework. Another challenge of control of hydraulic actuated exoskeleton is how to compensate for the input saturation caused by the hydraulic actuator, which in principle might lead to poor tracking performance, including longer period of transient, unacceptable overshoot, even larger tracking error.…”
Section: Introductionmentioning
confidence: 99%